Perilaku self-management dengan kejadian ulkus diabetikum pada pasien diabetes mellitus tipe 2 - Eka Yudha Chrisanto; Agustama Agustama (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Self-management behaviour of diabetic foot ulcer occurrence among patient with type 2 diabetes mellitusBackground: Diabetes mellitus is one of the silent killers. Indonesia is a country with the 4th largest number of people with diabetes mellitus after China, India, and the United States. In Indonesia people with diabetes mellitus increased from 8.4 million in 2000 to 21.3 million in 2030.Purpose: To determine the self-management behaviour and diabetic foot ulcer occurrence among patient with type 2 diabetes mellitus.Method: A quantitative research type, with cross sectional analytic and analytical research designs. The population of all people with diabetes mellitus as many as 432 people and a sample of 38 people with a total sampling technique. Data collection using questionnaire sheets and statistical tests used were Chi-Square statistical tests.Results: The frequency distribution of the incidence of diabetic ulcers in patients with type 2 diabetes mellitus, with the category of diabetic ulcers occurring as many as 14 respondents (36.8%). Diabetes diet adherence in patients with diabetes mellitus, with the category of non-compliance with 16 respondents (42.1%). Monitoring blood sugar levels in patients with type 2 diabetes mellitus, with non-routine categories of 15 respondents (39.5%). Physical activity in patients with type 2 diabetes mellitus, with a less good category of 19 respondents (50%).Conclusion: There is a relationship between blood sugar and diabetic ulcer diabetes in type 2 diabetes mellitus patients. There is a relationship between diabetes diet and diabetic ulcer diabetes in type 2 diabetes mellitus patients. There is a relationship between physical activity and the incidence of diabetic ulcers in patients with type 2 diabetes mellitus. It is expected that DM patients can routinely carry out physical and routine activities with high salt levels) in health care facilities and carry out a diabetes diet in accordance with the rules proposed by nutritionists.Keywords: Self-management; Behaviour; Diabetic foot ulcer; Occurrence; Patient; Type 2 diabetes mellitusPendahuluan: Diabetes melitus salah satu the silent killer. Indonesia merupakan negara dengan jumlah penderita diabetes melitus ke-4 terbanyak setelah Cina, India, dan Amerika Serikat.di Indonesia penyandang diabetes melitus mengalami kenaikan dari 8,4 juta pada tahun 2000 menjadi 21,3 juta pada tahun 2030.Tujuan: Diketahui hubungan perilaku self-management dengan kejadian ulkus diabetikum pada pasien diabetes mellitus tipe 2Metode: Jenis penelitian kuantitatif, dengan rancangan penelitian analitik dan pendekatan cross sectional. Populasi seluruh seluruh penderita diabetes melitus sebanyak 432 orang dan sampel sebanyak 38 orang dengan teknik total Sampling. Pengumpulan data menggunakan lembar kuesioner dan Uji statistik yang digunakan adalah uji statistik Chi-Square.Hasil: Distribusi frekuensi kejadian ulkus diabetikum pada penderita diabetes melitus tipe 2, dengan kategori terjadi ulkus diabetikum sebanyak 14 responden (36,8%). Kepatuhan diet diabetes pada pasien diabetes melitus, dengan kategori tidak patuh sebanyak 16 responden (42,1%). Pemantauan kadar gula darah pada pasien diabetes melitus tipe 2, dengan kategori tidak rutin sebanyak 15 responden (39,5%). Aktivitas fisik pada pasien diabetes melitus tipe 2, dengan kategori kurang baik sebanyak 19 responden (50%).Simpulan: Ada hubungan pemantauan kadar gula darah dengan kejadian ulkus diabetikum pada pasien diabetes melitus tipe 2. Ada hubungan kepatuhan diet diabetes dengan kejadian ulkus diabetikum pada pasien diabetes melitus tipe 2. Ada hubungan aktivitas fisik dengan kejadian ulkus diabetikum pada pasien diabetes melitus tipe 2. Diharapkan pasien DM agar rutin melakukan aktivitas fisik serta rutin mengontrol kadar gula darah pada fasilitas pelayanan kesehatan Serta menjalankan diet diabetes sesuai dengan aturan yang disarankan ahli gizi.